Gender, Power and Politics in Agriculture - Njuki, Jemimah; Tufan, H.A.; Polar, Vivian; Campos, Hugo; Morgan-Bell, M. (2025)
This is a open access book. In the agriculture sector, the language of gender integration often ignores the politics and the power dynamics that are central to critical, and feminist, analysis of gender relations. This volume explores largely neglected topics such as power dynamics, masculinities, gendered social norms, feminist research practice, intersectionality, critical analysis of tools and more, that are fundamental to shifting the entrenched power dynamics and politics of gender research in agriculture. The purpose of this book is to reduce the gap existing between theory, methods, and practice of gender relations in agriculture and agricultural research. Through an in-depth analysis of current processes in agriculture and drawing on existing experiences in other sectors, it seeks to create pathways for learning, catalyzing change and positive impact on gender equity and social inclusion. This volume seeks to bring forth a change in how gender relations in agriculture are researched, practiced and taught.